2011
DOI: 10.1002/syn.20906
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional synaptic plasticity induced by conditioned stimulations with different number of pulse at hippocampal CA1 synapses: Roles ofN‐methyl‐D‐aspartate and metabotropic glutamate receptors

Abstract: In the mammalian brain, the hippocampus has been established as a principle structure for learning and memory processes, which involve synaptic plasticity. Although a relationship between synaptic plasticity and stimulation frequency has been reported in numerous studies, little is known about the importance of pulse number on synaptic plasticity. Here we investigated whether the pulse number can modulate bidirectional plasticity in hippocampal CA1 areas. When a CA1 area was induced by a paired-pulse (PP) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The use of PKC and mTORC1 inhibitors, at concentrations that do not affect memory on their own, demonstrated the independent mechanisms underlying the short-term (PKC signaling) and long-term (mTORC1 signaling) object-recognition memory deficits produced by THC. In this regard, PKC signaling has been shown to regulate synaptic plasticity at CA1 synapses (Hsu et al, 2011). At this level, PKC signaling is implicated in facilitating longterm plasticity by reducing the threshold necessary for longterm potentiation induction (Miura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The use of PKC and mTORC1 inhibitors, at concentrations that do not affect memory on their own, demonstrated the independent mechanisms underlying the short-term (PKC signaling) and long-term (mTORC1 signaling) object-recognition memory deficits produced by THC. In this regard, PKC signaling has been shown to regulate synaptic plasticity at CA1 synapses (Hsu et al, 2011). At this level, PKC signaling is implicated in facilitating longterm plasticity by reducing the threshold necessary for longterm potentiation induction (Miura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al (2011) suggested recently that “CA1 synaptic plasticity is regulated by the result of competition between NMDARs and mGluR5 receptors”. Although a similar competition is likely to occur also between NMDARs and mGluR1, an interaction between mGluR1 and metabotropic NMDAR actions cannot be simply explained by data from published studies because they are exclusively based upon the use of the competitive NMDAR antagonist D-AP5 which does not allow to distinguish between ionotropic and metabotropic NMDAR actions.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that induction of LTP and LTD depends on different levels of postsynaptic Ca 2+ increasing through NMDAR, metabotropic glutamate receptor or voltagegated Ca 2+ channel activation (Neveu and Zucker, 1996;Artola and Singer, 1993;Hansel et al, 1997;Malenka and Nicoll, 1999;Yang et al, 1999;Zucher, 1999;Cormier et al, 2001;Cho et al, 2001;Lisman, 2001;Gall et al, 2005;Anwyl, 2006;D'Errico et al, 2009;Fujii et al, 2010;Vogt and Canepari, 2010;Hsu et al, 2011) and decreasing by buffering mechanisms (Malenka et al, 1992;Gold and Bear, 1994). On this ground, we can suggest that in the vestibular neurons a change in the IBI modifies the ratio between Ca 2+ enhancement during the stimulus, due to the NMDAR and/or voltage-dependent Ca 2+ channel influx (Serafin et al, 1991;Takahashi et al, 1994b), and its decay during the pause, leading to different postsynaptic Ca 2+ levels.…”
Section: Discussionmentioning
confidence: 99%